Early medieval Jewish policy in Western Europe - Bachrach, Bernard S., 1939- (University of Minnesota Press, 1977)
Early Medieval Jewish Policy in Western Europe was first published in 1977. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This is the first study of early medieval Jewish policy in the West which examines the nature of this policy from the perspective and aims of its formulators. As the author points out, most specialists in Jewish history have been dominated by what the historian Salo Baron has called the "lachrymose conception, ' a view which emphasized persecution and suffering as a fundamental theme of Jewish history. Professor Bachrach challenges this view and attacks what he calls the myth of Christian church domination of the early medieval world.